The effect of Aloe Vera gel on prevention of pressure ulcers in patients hospitalized in the orthopedic wards: a randomized triple-blind clinical trial - Davood Hekmatpou; Fatemeh Mehrabi; Kobra Rahzani; Atefeh Aminiyan (BMC, 2018)
Abstract Background One of the most common orthopedic problems is the incidence of pressure ulcer followed by immobility. This study aimed to investigate the effect of Aloe Vera gel on the prevention of pressure ulcer in patients hospitalized in the orthopedic ward. Method This study is a randomized, triple-blind clinical trial which was done on 80 purposefully selected patients in orthopedic ward in Arak town, Iran, 2016. Patients were randomly assigned into two intervention and control groups based on blocking sampling method. In each group the routine daily cares to prevent bed sores were performed by nurses. In the intervention group in addition to routine nursing care to prevent bed sores, twice a day (hours of 9 and 21) pure Aloe Vera gel on the areas of hip, sacrum and heel were rubbed, but in the control group placebo (gel of water and starch) were used. Then sacral, hip and heel of both groups on days 3, 7 and 10 for of signs of pressure ulcers was evaluated. Results The mean age of patients in the control group was (42.34 ± 12.19) and in the intervention group Was (41.71 ± 11.50) years, respectively. In the intervention group 1 patient afflicted with sore of hip and two people with sacral pressure ulcer. In the control group 3 patients affiliated with sore of hip, 8 people with sacral pressure ulcer, and 1 person had pressure sore of heel. Analysis of the data showed that both groups had statistically significant differences in the incidence of pressure ulcers (P = 0.047). This means that Aloe Vera gel could prevent the occurrence of pressure ulcers in the intervention group. Conclusion Due to the effect of Aloe Vera gel to prevent a rise in temperature, non-blanchable redness, swelling and pain of the skin of regions under study in hospitalized patients in the orthopedic ward, applying of it toward the prevention of pressure ulcers in patients at risk of pressure ulcer development is recommended. Trial registration This study was registered in Iranian Registry of Clinical. Trials in 07/09/2016 with the IRCT ID: IRCT2016051027825N1.